Neighboring Mode‐Dependent Dynamic Event‐Triggered Control for Markov Jump Interconnected Systems With Unknown Interconnections - Li, Li‐Wei; Lv, Huifang; Shen, Jie; Shen, Mouquan (International journal of robust and nonlinear control, 2025)
ABSTRACT This work is absorbed in the neighboring mode‐dependent event‐triggered control scheme for Markov jump systems with unknown interconnections. To save communication resources and reduce cost, a dynamic event‐triggered scheme relies on neighboring modes information is proposed. Then, the state feedback controllers are designed based on neighboring mode–dependent dynamic event‐triggered approach to assure the stability of the system. Distinguished from existing results, the proposed method does not need to access the operation modes of all sub‐systems. The cyclic‐small‐gain criterion is used to tackle the unknown interconnections, thereby a novel stability criteria are obtained for the closed‐loop systems with H∞$$ H_{∞ } $$ performance. Finally, two simulation results are given to reveal the validity of the obtained results.